Graphene oxide and its derivatives as potential Ovchinnikov ferromagnets - Ali, Anzar (IOP Science, 2021)
Ovchinnikov postulated the possibility of ferromagnetism in organic compounds having a mixed density of sp3 and sp2 carbon atoms. Such systems provide an interesting avenue for exploring magnetism in the absence of the quintessential d- and f-block elements as ingredients. As graphene oxide (GO) and its derivatives naturally possess a mixture of sp3 and sp2 carbon atoms, it is pertinent to look at them as potential candidates for Ovchinnikov ferromagnetism. We have looked at the evolution of magnetic property in a series of GO samples with a gradual increase in the degree of oxidation and hence the sp3/sp2 fraction. Starting with a GO sample with a high sp3/sp2 ratio, we utilize chemical reduction technique to prepare another set of reduced graphene oxide (rGO) samples. Magnetization measurements on these samples further illustrate the importance of sp3/sp2 fraction on magnetic behavior suggesting GO and its derivatives as a potential Ovchinnikov ferromagnet candidate. The evolution of magnetic moment with sp3/sp2 carbons can be utilized in carbon based spintronic applications.
Only IISERM authors are available in the record
Keywords: Graphene oxide; derivatives; potential; Ovchinnikov